PEMBELAJARAN KOOPERATIF DALAM MENINGKATKAN INTELIGENSI INTERPERSONAL - Ishmatun Nihayah (TA'LIM : Jurnal Studi Pendidikan Islam, 2020)
Cooperative learning is one of the learning models that places students as subjects of learning (student oriented). With a democratic classroom atmosphere, learning to give each other opportunities gives more opportunities to the maximum potential of students. Five elements in the cooperative learning model must be applied. The five elements are first, positive interdependence. Second, personal responsibility (personal responsibility). Third, face totale promotive interaction (promotive reaction). Fourth, interpersonal skills (communication between members), and to Five group processing (group processing). Whereas in interpersonal intelligence there are three dimensions that must be fulfilled, the first is Social sensitivity or social sensitivity, namely the ability of children to be able to feel and observe the reactions or changes in others that they show both verbally and non-verbally. Second, Social insight, which is the ability of children to understand and seek effective problem solving in a social interaction, so that these problems do not hamper let alone destroy the social relations that have been built by children. The third, social communication or mastery of social communication skills is the ability of individuals to use the communication process in establishing and building healthy interpersonal relationships. In the process of creating, building and maintaining social relations, then someone needs the ingredients. Therefore, researchers want to conduct a literature study that reveals that the holding of cooperative learning in an educational institution, there is an increase in interpersonal intelligence